A struggle for distributive fairness in waste disposal: Koto Ward and In-Ward Waste Disposal in the 23 wards of Tokyo. Issue 2 (1st February 2017) - Nakazawa, Takashi
ABSTRACT: This study explores the politics of distributive fairness in Locally-Unwanted-Land-Uses (LULUs) siting by looking into how a movement in LULU disputes changes its attitude towards a frame of distributive fairness over a long period of time. Some kinds of facilities are often opposed by local residents because of negative side-effects, even as they are claimed to be necessary for the well-being of the wider public. Framing refers to actors' signifying work, and how to frame distributive fairness plays a significant role in conflicts over such controversial land uses. In the 23 wards of Tokyo, distributive fairness in waste disposal among the wards has been a crucial issue. In the early 1970s, Koto Ward, which suffered a disproportionate burden of waste disposal, launched a campaign to rectify the unfairness. In-Ward Waste Disposal (IWWD), a frame of distributive fairness, played a central role in this movement. However, Koto Ward's attitude towards this frame of distributive fairness changed over time. By examining why Koto Ward's advocacy for IWWD varied over time, this study shows how Koto Ward's stance on IWWD changed in conjunction with economic, policy, and political circumstances, thereby illuminating the importance of integrating socio-politico-economic contexts in framing analysis.